PENGIMBUHAN KATA DALAM BAHASA KEDAYAN BEKENU, MIRI - Nur Izzah Alwani, Sab (Universiti Malaysia Sarawak (UNIMAS), 2025)
This study aims to describe one of the morphological processes, namely verb affixation in Kedayan Language. The objective of this study is to identify the types of verb affixes to form derived words in Kedayan Language and describe the function of each affix in Kedayan Language. This study is qualitative in nature with a descriptive approach that describes verb affixes in Kedayan Language. Data were collected from 5 informants consisting of residents of Kampung Bukit Kawang in Bekenu District, Miri who were selected based on the set criteria. There were 100 verbs selected from the Swadesh list. Asmah Haji Omar Structural Approach was used in this study. The findings of the study are that there are 11 prefix affixes in the Kedayan language, consisting of the affixes [me-], [mem-], [men-], [meng], [di-], [be-], [te-], [pe-], [pem-], [pen-] and [peng-], three suffix affixes, namely the affixes [-an], [-kan] and [-i] and four affixes, namely the affixes [meN...-kan], [be-...-an], [di-...-kan] and [meN-...-i]. Furthermore, verb affixes in the Kedayan language have active inflectional and derivational functions, which refer to actions that are happening or have already happened, as well as affixes that cause word class changes. A total of 100 original lexical verbs in the Kedayan language have been collected based on the Swadesh verb list. This study describes in depth the function of affixes on verbs in the Kedayan language and explains in detail the morphological structure and aspects of the language.